The Relationship between Husband's Support and Antenatal Care Visits for Pregnant Women at Langsat Health Center (HEALTH CARE: JURNAL KESEHATAN, 2024)
Antenatal care examination is assessed by looking at the coverage figures of K1 (Initial visit) K4 (Re visit). The low coverage of ANC in pregnant women is due to several factors such as age, education, parity, distance of pregnancy, distance of health facilities, knowledge, economic status and husband support. The purpose of this study was to determine the Relationship between Husband Support and Antenatal Care Visits for Pregnant Women During the Covid-19 Pandemic in the Langsat Health Center Work Area. This type of research is quantitative using a descriptive research design design correlation with a crosectional approach.this research instrument uses a husband support questionnaire sheet consisting of 15 questions. This study used univariate analysis and bivariate analysis, using chi-square test to determine the relationship of variables. The results of the studyfound that respondents received husband support as much as 56.9% and complete ANC visits as much as 74.5%. The results of the statistical test that have been carried out have been obtained p valueI of 0.000 > 0.005 meaning that there is a significant relationship between husband support and antenatal care visits. This study recommends to husbands to be more supportive in terms of pregnancy checkups.